2019
DOI: 10.1097/md.0000000000016884
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment of coronary heart disease angina pectoris with Chinese patent medicine

Abstract: Background:Patients with coronary heart disease (CHD) angina pectoris are in critical condition, which can cause sudden death, myocardial infarction, and other adverse events, and bring serious burden to families and society. Timely treatment should be given to improve the condition. Western medicine treatment of angina pectoris failed to meet the demand of angina symptom control.Objective:It is hoped that the research method with higher evidential value will be adopted to compare the short-term, medium-term, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…AP is one of the main types of CHD with irregular episodes and pain radiating to the shoulder and neck during attacks. Factors such as overwork, mood disorders, and climate change are potential triggers for the development of the disease, and if not treated in a timely manner, there is a high risk of developing acute myocardial infarction which may lead to a significant increase in the risk of death [ 10 , 11 ]. Pharmacological treatment is a conventional therapy in Western medicine, which mainly focuses on 3 aspects: dilating diseased blood vessels, improving atherosclerosis, and lowering blood pressure, with the purpose of reducing myocardial oxygen consumption, delaying atherosclerotic lesions, improving myocardial blood supply, and thus relieving angina symptoms and reducing mortality [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…AP is one of the main types of CHD with irregular episodes and pain radiating to the shoulder and neck during attacks. Factors such as overwork, mood disorders, and climate change are potential triggers for the development of the disease, and if not treated in a timely manner, there is a high risk of developing acute myocardial infarction which may lead to a significant increase in the risk of death [ 10 , 11 ]. Pharmacological treatment is a conventional therapy in Western medicine, which mainly focuses on 3 aspects: dilating diseased blood vessels, improving atherosclerosis, and lowering blood pressure, with the purpose of reducing myocardial oxygen consumption, delaying atherosclerotic lesions, improving myocardial blood supply, and thus relieving angina symptoms and reducing mortality [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic criteria for CHD angina pectoris: Based on the guidelines formulated by the American College of Cardiology and the American Heart Association (ACC/AHA) in the Guidelines for the Treatment of Chronic Stable Angina Pectoris (2007) and the Guidelines for the Management of Patients with Unstable Angina Pectoris and Non-ST-Elevation Myocardial Infarction (2011), and referring to the Guidelines for the Diagnosis and Treatment of Chronic Stable Angina Pectoris in China in 2007 and the Guidelines for the Diagnosis and Treatment of Unstable Angina Pectoris and Non-ST-Elevation Myocardial Infarction in China in 2007, and the Standard for the Consensus of Integrative Medicine for Integrative Medicine for the Treatment of CHD (2019). [ 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…Li et al [26] suggested a new type of machining method for granite rocks. They try to achieve more cost-effective machining by keeping tribological interactions to a minimum.…”
Section: Introductionmentioning
confidence: 99%